Hydrogen sulfide protects against endoplasmic reticulum stress and mitochondrial injury in nucleus pulposus cells and ameliorates intervertebral disc degeneration. (March 2017) - Xu, Daoliang; Jin, Haiming; Wen, Jianxia; Chen, Jiaoxiang; Chen, Deheng; Cai, Ningyu; Wang, Yongli; Wang, Jianle; Chen, Yu; Zhang, Xiaolei; Wang, Xiangyang
Graphical abstract: Abstract: It has been suggested that excessive apoptosis in intervertebral disc cells induced by inflammatory cytokines, such as interleukin (IL)-1β, is related to the process of intervertebral disc degeneration (IVDD). Hydrogen sulfide (H2 S), a gaseous signaling molecule, has drawn attention for its anti-apoptosis role in various pathophysiological processes in degenerative diseases. To date, there has been no investigation of the correlation of H2 S production and IVDD or of the effects of H2 S on IL-1β-induced apoptosis in nucleus pulposus (NP) cells. Here, we found that the expression levels of cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE), two key enzymes in the generation of H2 S, were significantly decreased in human degenerate NP tissues as well as in IL-1β-treated NP cells. NaHS (H2 S donor) administration showed a protective effect by inhibiting the endoplasmic reticulum (ER) stress response and mitochondrial dysfunction induced by IL-1β stimulation in vitro, the effect was related to activation of the PI3K/Akt and ERK1/2 signaling pathways. Suppression of these pathways by specific inhibitors, LY294002 and PD98059, partially reduced the protective effect of NaHS. Moreover, in the percutaneous needle puncture disc degeneration rat tail model, disc degeneration was partially reversed by NaHS administration. Taken together, our results suggest that H2 S plays a protective role in IVDD and the underlying mechanism involves PI3K/Akt and ERK1/2 signaling pathways-mediated suppression of ER stress and mitochondrial dysfunction in IL-1β-induced NP cells.